How did Immigrants Fare in the Irish Labour Market over the Great Recession? - Kelly, Elish; McGuinness, Seamus; O’Connell, Philip J.; González Pandiella, Alberto; Haugh, David (The Economic and Social Review, 2020)
This paper examines the impact of the Great Recession on labour market outcomes for Irish immigrants compared to natives and how this relationship evolved afterwards. We find that the employment chances of immigrants decreased significantly over the recession and, on average, this persisted during the recovery. We also find that their relative unemployment risk increased, while there was substantial variation in these patterns between immigrants. Immigrants from the United Kingdom fared particularly badly during the recession. Their unfavourable outcomes intensified in the recovery, particularly among non-naturalised UK immigrants. African immigrants showed the highest employment penalties and unemployment risks during the recession but in the recovery these negative outcomes were confined to naturalised African immigrants. The recovery trends appear to be related to composition effects, as many refugees with weak labour market attachment became naturalised citizens during the recession. This suggests that the difficulties some immigrants experience in the labour market would be underestimated without taking due account of naturalisation processes.